Pengaruh Kompetensi terhadap Kualitas Pelayanan Administrasi Kelurahan Setiamanah Kota Cimahi - Safarry, Learian; Suteja, Kurniawati; Suhendar, Atep (Universitas Batanghari Jambi, 2024)
Community services are various government organizations engaged in services whose job is to provide services for public. Public services in question are various forms of service-related activities carried out by an organization or individual. Every organization is formed to achieve certain goals, and if these goals are achieved, the organization can be said to be successful. Competence is a strong foundation for achieving success. Employee competence is needed when carrying out services. The services provided to the community are part of the identity of the organization. If in providing services, there is a good impression from its employees, then the organization looks good in the eyes of the public. This study aims to determine how competence influences the quality of administrative services in the Setiamanah Village, Cimahi City. The method in this study used quantitative methods with a population and sample of 21 employees. The data analysis technique used in this study is a simple linear regression analysis technique. Based on the partial linear regression test summary model table above it proves that the magnitude of the R Square correlation value is 0.600 or 60%. This means that the influence of competence on the quality of administrative services is 60%. And 40% is influenced by other factors that are not present in this study.